Cytokeratin 18 (CK18) and CK18 Fragments for Detection of Minimal Residual Disease in Colon Cancer Patients - Olszewski-Hamilton, Ulrike; Buxhofer-Ausch, Veronika; Ausch, Christoph; Hamilton, Gerhard (IntechOpen, 2012)
None